2018
DOI: 10.1111/ens.12330
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of rotund gene through larval RNA interference affects genital and elytral morphology in the ground beetle Carabus maiyasanus (Coleoptera: Carabidae)

Abstract: Interspecific variation in genital morphology contributes to prezygotic reproductive isolation in many insect species. However, developmental genes affecting genital morphology are poorly understood. We undertook larval RNA interference (RNAi) experiments with rotund (rn) gene in the ground beetle Carabus (Ohomopterus) maiyasanus to examine the knockdown effects of this gene on genital development. We injected double‐stranded RNA (dsRNA) into third instar larvae of C. maiyasanus. The injection of rn dsRNA resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…An elevated rn expression may be required for the extension of the copulatory piece. On the other hand, rn RNAi did not affect the development of female genitalia ( 27 ). This is consistent with the results of QTL mapping, which indicated that the genetic basis of the development of genital parts differs between the sexes.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…An elevated rn expression may be required for the extension of the copulatory piece. On the other hand, rn RNAi did not affect the development of female genitalia ( 27 ). This is consistent with the results of QTL mapping, which indicated that the genetic basis of the development of genital parts differs between the sexes.…”
Section: Discussionmentioning
confidence: 95%
“…Higher expression of these genes may be involved in elongation of the copulatory piece in C. maiyasanus . The rn transcription factor particularly is necessary for the development of various appendages and wings in Drosophila , and we found that the rn gene knockdown via larval RNA interference (RNAi) suppressed the formation of the copulatory piece in C. maiyasanus ( 27 ). An elevated rn expression may be required for the extension of the copulatory piece.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, it is important to identify genes that are differentially expressed among species during genital morphogenesis to understand the genetic and developmental basis of species‐specific genital morphologies. However, knowledge regarding gene expression and function during genital development in Ohomopterus species is limited (Fujimaki et al ., ; Sota et al ., ; Fujisawa et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…The CP and VA in Ohomopterus ground beetles have been studied in behavioral and evolutionary contexts, including the identification of candidate genes or genomic regions associated with genital diversification (Fujimaki et al, 2014; Fujisawa et al, 2019; Nomura et al, 2019; Sasabe et al, 2007, 2010; Sota et al, 2018). An understanding of the morphogenesis of genitalia, including spatio–temporal differences between species, can provide a precise framework for analyses of the differential expression and functions of candidate genes.…”
Section: Introductionmentioning
confidence: 99%